Dual Role of PTPN22 but Not NLRP3 Inflammasome Polymorphisms in Type 1 Diabetes and Celiac Disease in Children - Smigoc Schweiger, Darja; Goricar, Katja; Hovnik, Tinka; Mendez, Andrijana; Bratina, Natasa; Brecelj, Jernej; Vidan-Jeras, Blanka; Battelino, Tadej; Dolzan, Vita (Frontiers in Pediatrics, 2019)
Genetic polymorphisms in genes coding for inflammasome components nucleotide-binding oligomerization domain leucine rich repeat and pyrin domain-containing protein 3 (NLRP3) and caspase recruitment domain-containing protein 8 (CARD8) have been associated with autoinflammatory and autoimmune diseases. On the other hand several studies suggested that NLRP3 inflammasome contributes to maintenance of gastrointestinal immune homeostasis and that activation of NLRP3 is regulated by protein tyrosine phosphatase non-receptor 22 (PTPN22). PTPN22 polymorphism was implicated in the risk for various autoimmune diseases including type 1 diabetes (T1D) but not for celiac disease (CD). The aim of our study was to evaluate the role of inflammasome related polymorphisms in subjects with either T1D or CD as well as in subjects affected by both diseases. We examined PTPN22 rs2476601 (p.Arg620Trp), NLRP3 rs35829419 (p.Gln705Lys), and CARD8 rs2043211 (p.Cys10Ter) in 69 subjects with coexisting T1D and CD, 65 subjects with T1D who did not develop CD, 67 subjects diagnosed only with CD and 127 healthy unrelated Slovenian individuals. All results were adjusted for clinical characteristic and human leukocyte antigen (HLA) risk. PTPN22 rs2476601 allele was significantly more frequent among subjects with T1D (Padj=0.001) and less frequent in subjects with CD (Padj=0.039) when compared to controls. In patients with coexisting T1D and CD this variant was significantly less frequent compared to T1D group (Padj=0.010). Protective effect on CD development in individuals with T1D was observed only within the low risk HLA group. On the other hand, we found no association of NLRP3 rs35829419 and CARD8 rs2043211 with the development of T1D, CD or both diseases together. In conclusion PTPN22 rs2476601polymorphism was significantly associated with the risk of developing T1D in Slovenian population, while no associations of proinflammatory NLRP3 and CARD8 polymorphisms with T1D and CD were observed. Interestingly, the same PTPN22 variant protected from CD. We hypothesize that this effect may be mediated through the NLRP3 inflammasome activation.